Pliocene crocodiles from Kanapoi, Turkana Basin, Kenya. Issue 140 (March 2020) - Brochu, Christopher A.
Abstract: Three crocodylid species are known from the Pliocene Kanapoi locality in the western Turkana Basin. One of these, Crocodylus thorbjarnarsoni, includes material previously referred to Crocodylus niloticus (the modern Nile crocodile currently living in Lake Turkana) and Rimasuchus lloydi . C. thorbjarnarsoni was a gigantic horned crocodile similar in overall shape to most other generalized crocodylids, but its closest known relative is another extinct species, Crocodylus anthropophagus from the Pleistocene of Olduvai Gorge in Tanzania. It is not closely related to C. niloticus . The second is an extinct form of sharp-nosed crocodile ( Mecistops ), a group of slender-snouted crocodylids currently restricted to western and central Africa. The third is Euthecodon, a crocodylid with an extremely long, slender, and distinctively notched snout. Euthecodon and C. thorbjarnarsoni are known from substantial numbers of specimens, but only one Mecistops specimen has been identified from the locality. The crocodylian fauna at Kanapoi is taxonomically similar to that of most other Plio-Pleistocene fluviolacustrine deposits in the Turkana Basin. Crocodylian diversity in the Turkana region contracted from a peak of five co-existing species in the late Miocene to one today; this contraction was underway by the early Pliocene, but crocodylian diversity remained stable at three species until well into the Quaternary.